Gênero e empatia como moduladores dos processos de decisão social no Ultimatum Game: um estudo comportamental e eletrofisiológico - Campanhã, Camila (2014)
Because we live in society, constantly choices are relate not only our personal interest. Recent study (CAMPANHÃ et a, 2011) was verify that he participants realize your friends as more fair than an unknown, showing a unreleased information in the social decision making studies. Preview studies demonstrated the relation between an event-related potential, the Medial Frontal Negativity (MFN), in the unfair offers to unknown proposers, however not by friends. Beside this, the sLORETA analysis revealed a significant difference in the medial prefrontal cortex region - related to empathy and metallization - in the unknown condition when compared the unfair offers with the fair offers, however, not in the friend condition. The difference in the unfair perception related to the proposer introduces a new question about the widely accept altruistic punishment concept. Therefore, the present study aimed (i) to investigate the empathy and gender impact as modulators factors in the Ultimatum Game (UG) when the interaction is with a trustworthy person (friend) and an unknown; (ii) to investigate the behavior characterized as altruistic punishment in the adapted UG in two different interaction context. Thus, was realized two experiments. The first one, similar the anterior one, the participants played the UG with a friend and an unknown. Therefore, we controlled the empathy level (low and high) and gender. In the second experiment, beside the gender and empathy level control, the participants had to decide whether accept or reject the share proposals the R$120,00 reias between three persons: the proposer, the participant and a third person ( dummy ), that was a friend and a unknown in the first part of the game. In the second part of the game, the participants only decide whether accept or reject in the place of the friend and an unknown and don´t had any earnings and any loss involved. As results, was observed large rate of rejection the unfair offers proposed by an unknown than by the friend. The friend was judged as more fair. Also, was observed that the men reject more offers made by an unknown. The participants with high level of empathy rejected more unfair offers that was made by an unknown and presented the MFN amplitude more negative for unknown proposer and more positive for friend proposer. The men with high level of empathy presented the MFN amplitude more negative for the unknown. In the second experiment, the participants rejected more unfair proposals for both kind of third part. The MFN amplitude was more negative when the proposals were unfair for both (the participant and the third part). As well as women and for high empathy level participants. In the second part of the experiment two, the participants benefited more the friend. The MFN amplitude was more negative for the men in the interaction unknown proposing to the friend. The women presented more large P3 amplitude in the interaction unknown proposing to the friend. Taken together, the results suggest that the empathy and gender impact when a friend is involved. Beside this, the personal gains and losses involvement also was an important factor in the fairness perception. The present study corroborates with preview studies that showed the fairness perception modulated the trust and that he empathy and gender are factors with more or less impact in different context.